Anisotropic Optical Response of Silver Nanorod Arrays: Surface Enhanced Raman Scattering Polarization and Angular Dependences Confronted with Ellipsometric Parameters - Martin Šubr (Nature Portfolio, 2017)
Abstract Silver nanorod arrays prepared by oblique angle deposition (AgOADs) represent versatile, simple and inexpensive substrates for high sensitivity surface enhanced Raman scattering (SERS) applications. Their anisotropic nature suggests that their optical responses such as the SERS signal, the depolarization ratio, reflectivity and ellipsometric parameters critically depend on the states of polarization, nanorod angular arrangement and specific illumination-observation geometry. SERS polarization and angular dependences of AgOADs were measured using methylene blue (MB) molecule. Our study constitutes, to our knowledge, the most detailed investigation of such characteristics of plasmonic nanostructures to date. This is due to the 90°-scattering geometry used in which two out of three Euler angles determining the nanorod spatial orientation and four polarization combinations can be varied simultaneously. We attributed the anisotropic optical response to anisotropic (pseudo)refractive index caused by different periodicity of our structures in different directions since the plasmonic properties were found rather isotropic. For the first time we demonstrate very good correspondence between SERS intensities and ellipsometric parameters for all measured configurations as compared on the basis of the surface selection rules. Obtained results enable quantitative analysis of MB Raman tensor elements, indicating that the molecules adsorb predominantly with the symmetry axis perpendicular to the surface.